The Effectiveness of Mahogany (Swietenia macrophylla) Plantation Forest on Controlling Erosion and Runoff - Paimin, P (Forum Geografi, 2005)
Ecosystem of forest has been considered the most effective measures in controlling soil erosion and runoff. However, man-made forest or plantation forest is frequently disturbed that causing susceptible to land degradation, especially by erosion. The role of forest to protect soil from erosion forces is not only played by individual forest stand itself but also its community. Composition of vegetation community always change dynamically depending on the forest management system applied and the age of plant. To determine the effectiveness of mahogany forest plantation during its growth on controlling soil erosion and runoff, a study was conducted at mahogany plantation forest area of Gundih district. Three different ages of mahogany (1, 4, and 8 year old) were selected as observation plots. Soil erosion and runoff measurements were carried out on a small plot procedure of 4m x 22.1 m size. Whereas, observations on main tree of mahogany characteristics and its undergrowth vegetationâs were also accomplished within this area. The results indicated that the number and kind (species) of vegetation community of mahogany changed dynamically and tended to decrease as the main forest stand became older. The older mahogany produced less both soil erosion and surface runoff. Soil erosion level on vegetation community of mahogany plantation, during two months observations, decreases as much as 39.3%, 9.8%, and 5.2% respectively for1, 4, and 8 year old of mahogany comparing to bare land (control plot) of 112.6 kg/plot (12.7 ton/ha). Additionally, surface runoff lowered at the mahogany age of 4 and 8 year as high as 33 %and 52% respectively comparing to control one, but surface runoff at the mahogany of 1 year old had no different from the control one. The main role of this condition was played by thick litter at 8 year old of mahogany, and by creeping grass, and other shrub at 4 year old of mahogany.